The Serbian Orthodox Church and Science in the 21st Century - Jovanović, Miloš M. (The journal of Eastern Christian studies, 2025)
This paper deals with symbolic struggles unfolding in Serbia, where the conflicting parties could be identified as the Serbian Orthodox Church and the "wider scientific community." The authors focus on the five years which produced debates over three concrete issues which involved a conflict between "religion" and "science" in the Serbian public space: the discussion on the theory of evolution in public schools (2017), covid-19 protective measures (2020), and the inclusion of topics related to gender and sexuality in elementary school biology textbooks (2022). These conflicts contributed to creating and consolidating the symbolic boundaries in Serbian society. The corpus of empirical data includes texts available on online news portals, and these have been subjected to discourse analysis. Special attention was given to the borders drawn around social groups and collective identities by "religion" and "science." Symbolic classifications frequently followed geopolitical rifts and conflicts.